The determinants of cross-border bank flows to emerging markets: new empirical evidence on the spread of financial crises - Sabine Herrmann; Dubravko Mihaljek (Bank of Finland, Institute for Economies in Transition (BOFIT), 2011)
This paper studies the nature of spillover effects in bank lending flows from advanced to the emerging market economies and identifies specific channels through which such effects occur. We examine a panel data set of cross-border bank flows from 17 advanced to 28 emerging market economies in Asia, Latin America and central and eastern Europe from 1993 to 2008. Our empirical framework is based on a gravity model of financial flows. We augment this model with global, lender and borrower country risk factors, as well as financial and monetary integration variables. The empirical analysis suggests that global as well as country specific factors are significant determinants of cross-border bank flows. Greater global risk aversion and expected financial market volatility have been the most important factors behind the decrease in cross-border bank flows during the crisis of 2007 08. The decrease in cross-border loans to central and eastern Europe was more limited compared to Asia and Latin America, in large measure because of the higher degree of financial and monetary integration in Europe, and relatively sound banking systems in the region. These results are robust to various specification, sub-samples and econometric methodologies
URN:NBN:fi:bof-201408071968
Keywords: 330